2002
DOI: 10.1046/j.1365-8711.2002.05651.x
|View full text |Cite
|
Sign up to set email alerts
|

The faint end of the galaxy luminosity function

Abstract: We present and discuss optical measurements of the faint end of the galaxy luminosity function down to M_R = -10 in five different local environments of varying galaxy density and morphological content. The environments we studied, in order of decreasing galaxy density, are the Virgo Cluster, the NGC 1407 Group, the Coma I Group, the Leo Group and the NGC 1023 Group. Our results come from a deep wide-angle survey with the NAOJ Subaru 8 m Telescope on Mauna Kea and are sensitive down to very faint surface-brigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
193
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(212 citation statements)
references
References 85 publications
(119 reference statements)
19
193
0
Order By: Relevance
“…With our SBF distance of 11.1 ± 0.9 Mpc we can now confirm this impression. The derived SBF distance is also in good agreement with the mean distance of 11 Mpc for the group (Trentham & Tully 2002). We note that there was not much of colour range found in the five fields we analysed to unambiguously apply the distance calibration.…”
Section: Ugc 5944 ([Fs90] 047)supporting
confidence: 76%
See 1 more Smart Citation
“…With our SBF distance of 11.1 ± 0.9 Mpc we can now confirm this impression. The derived SBF distance is also in good agreement with the mean distance of 11 Mpc for the group (Trentham & Tully 2002). We note that there was not much of colour range found in the five fields we analysed to unambiguously apply the distance calibration.…”
Section: Ugc 5944 ([Fs90] 047)supporting
confidence: 76%
“…This dwarf elliptical is located right in the densest region of the Coma I group (Binggeli et al 1990;Trentham & Tully 2002) about 10 degrees away from the northern boundary of the Virgo cluster. The heliocentric velocity of BTS 128 of v = 1139 ± 86 km s −1 (Wegner et al 2001) is in good agreement with the Coma I cluster.…”
Section: Bts 128mentioning
confidence: 99%
“…The faint end slope of a composite LF, averaged over 60 nearby galaxy clusters, reveals a similar value of α = −1.28 (De Propris et al 2003). Previous studies have suggested that indeed the faint end slope of the LF is independent of environment: Trentham & Tully (2002) show such an almost invariable faint end slope in their study of five different environments with varying galaxy density and morphological content. They find a composite faint end slope of α = −1.19 for their entire sample.…”
Section: Luminosity Functionsupporting
confidence: 53%
“…Another useful parameter for describing the LF shape is the dwarf-to-giant ratio (Phillipps et al 1998;Sánchez-Janssen et al 2008). We compared our data with the study of Trentham & Tully (2002), adopting their definition of the d/g ratio as d/g = N(−17 < M R < −11)/N(M R < −17). By taking the completeness correction into account, we obtain d/g = 4.1 ± 0.6.…”
Section: Luminosity Functionmentioning
confidence: 99%
“…It was found that the fraction of massive early-type galaxies (E/S0) and dwarf elliptical galaxies is higher in a dynamically more evolved system with high velocity dispersion (Trentham & Tully 2002;Tovmassian et al 2004;Tovmassian & Plionis 2009). Especially in the case of the NGC 3992 subgroup, which is the most dynamically evolved Ursa Major cluster subgroup, considering its high frequency of early-type galaxies, morphological transformation to early-type galaxies by interactions and merging between galaxies may have occurred more frequently in the early stages of its dynamical evolution than in the other subgroups.…”
Section: Environmental Effects In a Lower Density Clustermentioning
confidence: 99%